Prevalencia de Giardia Intestinalis en caninos y niños del distrito de Tarapoto - Torres Cubas, Veronica Isabel (2016)
The causes of great damage in both animals and man, which has an impact on the development and performance of the same, as well as the economy. Giardia intestinalis, a parasitic disease caused by Giardia intestinalis, is one of the most prevalent public health problems in developing countries, especially in rural areas where ecological conditions are conducive to its transmission. It affects children more frequently, producing from asymptomatic infections to severe cases of diarrhea and malabsorption syndrome (1). As we know our department of San Martin is no stranger to being able to acquire zoonotic risk diseases, which increases the prevalence in children that constitute a health problem. Therefore it is necessary to carry out studies on the prevalence or presence of this parasite in canines to evaluate the true impact that these can affect the health of the children. For this purpose, the present study aims to measure the prevalence of Giardia intestinalis in canines and children under 12 years of age; To establish the zoonotic nature in the district of Tarapoto